First determination of the valence band dispersion of CH3NH3PbI3 hybrid organic–inorganic perovskite. (7th June 2017) - Lee, Min-I; Barragán, Ana; Nair, Maya N; Jacques, Vincent L R; Le Bolloc'h, David; Fertey, Pierre; Jemli, Khaoula; Lédée, Ferdinand; Trippé-Allard, Gaëlle; Deleporte, Emmanuelle; Taleb-Ibrahimi, Amina; Tejeda, Antonio
Abstract: The family of hybrid organic–inorganic halide perovskites is in the limelight because of their recently discovered high photovoltaic efficiency. These materials combine photovoltaic energy conversion efficiencies exceeding 22% and low-temperature and low-cost processing in solution; a breakthrough in the panorama of renewable energy. Solar cell operation relies on the excitation of the valence band electrons to the conduction band by solar photons. One factor strongly impacting the absorption efficiency is the band dispersion. The band dispersion has been extensively studied theoretically, but no experimental information was available. Herein, we present the first experimental determination of the valence band dispersion of methylammonium lead halide in the tetragonal phase. Our results pave the way for contrasting the electronic hopping or the electron effective masses in different theories by comparing to our experimental bands. We also show a significant broadening of the electronic states, promoting relaxed conditions for photon absorption, and demonstrate that the tetragonal structure associated to the octahedra network distortion below 50 °C induces only a minor modification of the electronic bands, with respect to the cubic phase at high temperature, thus minimizing the impact of the cubic-tetragonal transition on solar cell efficiencies.